Perfect space-time block codes and high performance decoding algorithm - HU Jun-feng1; YANG Yuan1; ZHANG Hai-lin1 (Tongxin xuebao)
Based on the structure of perfect space-time block codes（STBC）,an equivalent vertical Bell Laboratories layered space-time（V-BLAST） decoding model was given.Minimum mean-square error decision feedback equalizer（MMSE-DFE） was used to preprocess this model and a decoder with boundary controlled Fano tree search algorithm was proposed.This decoder achieves almost maximum likelihood（ML） decoding performance and applies for any antenna configurations.For a wide range of signal-to-noise ratio（SNR）,the decoder has lower computational complexity than that of previously proposed near-ML decoders.Operating in complex number field,the decoder is robust for any constellations.The decoder can apply for any multi-input multi-output（MIMO） systems that can be transformed into an equivalent V-BLAST model.Simulation results demonstrate the excellent performance of the proposed decoder.